Analisis Yuridis Tindakan Consitutional Disobedience Terhadap Sistem Ketatanegaraan di Indonesia - Febryandri Ferdyansyah; Sunny Ummul Firdaus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2025)
This study aims to analyze the phenomenon of constitutional disobedience against the state system in Indonesia. Therefore, this study will discuss the factors that influence the occurrence of constitutional disobedience and its constitutional impact.The research methodology used by the author is normative legal research or doctrinal approach. The nature of the research used in this study is prescriptive. The approaches used in this study are the statue approach and case approach. In this study, the legal materials employed in this study consist of primary and secondary legal sources. The data collection technique applied is literature study. The data analysis technique used in this research uses deductive reasoning.The study finds that there are four factors influencing of constitutional disobedience, namely, the DPR and the Government do not always comply the Constitutional Court's rulings and there is a growing tendency toward the practice of autocratic legalism. The impacts of such constitutional disobedience include the weakening of constitutional supremacy, institutional delegitimization of the Constitutional Court, legal uncertainty in the implementation of Constitutional Court decisions, and the erosion of judicial independence due to political interference.